Chi's sweet adventures. 3 - Natsume, Kinoko; Konami, Kanata, 1958- (Vertial Comics, 2019)
Chi finds herself on an adventurous walk with Cocchi. When they find themselves running from a dog that gets off its leash, they just may have found an unlikely friend.